Mitigasi Risiko Supply Chain Rumput Laut Berdasarkan Perspektif Macroergonomics Analysis of Structure - Silvana Mohamad; Evi - Yuliawati (Program Studi Teknik Industri Universitas Setia Budi, 2023)
Indonesia, particularly East Indonesia, accounts for up to 85% of the world's wet seaweeds. Bulukumba is one of Indonesia's most important seaweed producing places. In Babana Hamlet, Bulukumba Regency, 80% of the people is employed as a seaweed grower. Coordination and cooperation between all supply chain actors for seaweed commodities in Bulukumba Regency is required to meet the needs of the market. Poor quality seaweed results in losses to farmers. If this happens, it will result in disruption of the supply chain network, and reduce the profits of the perpetrators. Macroergonomic Structure Analysis (MAS) consists of three main elements of a sociotechnical system, namely the technological subsystem, the personnel subsystem, and the external environment. The only subsystems used were the personnel subsystem and the external environment subsystem. The risk with the highest weight obtained was on the personal subsystem in the professionalism factor with a weight of 0.32 (Motivation decreased during the rainy season). For the external environment factor is a weight of 0.33 (Rainy Season) which is associated with the rainy season. This is because the rainy season has the worst effects. Then the drying process will also be interrupted. The production of seaweed breeders greatly influences the supply chain process. If the risk to seaweed farmers occurs, then the collector traders in carrying out the supply will take longer and the capacity to be transported will also be reduced. The answers found for improvement include picking seeds, acquiring a nursery, acquiring a laboratory, and establishing a landbase to prepare for adverse weather.